Izazovi produljenja ljudskoga života na razmeđu poboljšanja i agonije - Singbo, Odilon-Gbènoukpo; Gložinić, Terezija; Čartolovni, Anto (2020)
Ovaj rad nastoji prikazati dva načina produljenja ljudskoga života. S jedne strane nalazi se distanazija, tj. terapijska upornost oko produženja života teškoga bolesnika, a s druge strane transhumanizam kao filozofski pravac koji u svojoj srži teži bezgraničnom produžavanju ljudskoga života s temeljnom željom za eliminiranjem bolesti, starenja i smrti. Povezujući ih s medicinskom praksom, rad pokazuje implikacije u kliničkoj praksi te nastoji upozoriti na etička i antropološka pitanja o produžavanju života.
The main aim of this paper is to present two different forms of human life extension. On the one hand there is dysthanasia, i.e. therapeutic persistence in the provision of life-sustaining measures to terminally ill patients, and on the other hand, transhumanism as a philosophical viewpoint which in its core strives towards unlimited extension of human life with the fundamental desire to eliminate disease, ageing and death. By putting them in correlation with the healthcare practice, the paper points to implications in clinical practice and draws attention to ethical and anthropological issues in connection with life extension.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Distanazija -- Transhumanizam -- Medicinska tehnologija -- Produžavanje života -- Bolest -- Smrt -- Besmrtnost -- Bioetika